"Nano‐Fishnet" Structure Making Silk Fibers Tougher. (1st June 2016) - Liu, Ruchuan; Deng, Qinqiu; Yang, Zhen; Yang, Daiwen; Han, Ming‐Yong; Liu, Xiang Yang
Abstract : Based on the combined technologies of atomic force microscopy, X‐ray diffraction/scattering, Fourier transform infrared spectra analysis, etc., it is demonstrated that the nano‐fishnet‐like networks, one of the most flexible but toughest structures, turn out to be the basic structure of silk filaments. The force patterns of pulling individual fibrils allow the identification of the pathways of unfolding protein segments in stacking β‐crystallites, which reveal the fishnet‐like topology. The calculation shows that the β‐crystallites in silk nanofibrils are the cross‐linking points of the nano‐fishnets, which may enhance the toughness of silk filaments up to 1000 times, compared with amyloid‐like and unlinked string structures. It follows that the strong β‐sheet–β‐sheet interaction, a high degree of ordering, and a high density of β‐crystallites in silk fibers toughen the fishnet structure, then strengthen silk filaments, in consistency with the experiments for both spider and silkworm silks. The knowledge on the fishnet structure of silk fibers sheds light on the design and synthesis of either protein or synthetic fibers of ultraperformance in a more generic way. Abstract : The fishnet structure in silk fibrils determines the unusual mechanical performance of spider silk and silkworm silk fibers. Via the stacking of the secondary structure, the β‐crystallites give rise to the nano‐fishnets in silk fibrils, where stronger β‐sheet–β‐sheet interactions, the better alignment, and higher density of β‐crystallites enhance the mechanical performance of silk fibers.